A study on the determinants of brand loyalty in sport shoes among students - Nor Azah, Abdul Aziz (2019)
The purpose of the study is to explore the influence of brand satisfaction, brand trust, brand community, word of mouth and brand identification on brand loyalty in sports shoes among university students. A conceptual model was established based on existing literature to test the relationship between the variables of the study. A survey design using simple random sampling was used. A sample of 319 university students participated in this study. The results of correlation and regression analysis shows that all five independent variables (brand satisfaction, brand trust, brand community, word of mouth and brand identification) have a significant relationship and influenced brand loyalty in sports shoes among university students. The results also show that brand satisfaction is the most influential factor on brand loyalty related sports shoes among students. Hence, the proposed model offers a greater understanding of how brand satisfaction, brand trust, brand community, word of mouth and brand identification can be improve the brand loyalty among university students. Based on the result of this study, brand owners should produce good quality products to fullfil the customer needs and enhance customers loyal with the brand. Furthermore, managers need to build good relationships with the customers in order to build customer loyalty to the brand. Finally, limitations of the study were discussed in tandem with the suggestion for future research